The effects of environmental interventions for delirium in critically ill surgical patients - Hak-Jae Lee; Yoon-Joong Jung; Nak-Joon Choi; Suk-Kyung Hong (Acute and Critical Care, 2023)
Background Delirium occurs at high rates among patients in intensive care units and increases the risk of morbidity and mortality. The purpose of this study was to investigate the effects of environmental interventions on delirium. Methods This prospective cohort study enrolled 192 patients admitted to the surgical intensive care unit (SICU) during the pre-intervention (June 2013 to October 2013) and post-intervention (June 2014 to October 2014) periods. Environmental interventions involved a cognitive assessment, an orientation, and a comfortable environment including proper sleep conditions. The primary outcomes were the prevalence, duration, and onset of delirium. Results There were no statistically significant differences in incidence rate, time of delirium onset, general characteristics, and mortality between the pre-intervention and post-intervention groups. The durations of delirium were 14.4±19.1 and 7.7±7.3 days in the pre-intervention and post-intervention groups, respectively, a significant reduction (P=0.027). The lengths of SICU stay were 20.0±22.9 and 12.6±8.7 days for the pre-intervention and post-intervention groups, respectively, also a significant reduction (P=0.030). Conclusions The implementation of an environmental intervention program reduced the duration of delirium and length of stay in the SICU for critically ill surgical patients.